Pattern of consumption of psychoactive substances in alternative transport drivers - Branco, Fernanda (2021)
Introduction: Alternative transport drivers, better known as “pirates / pirateiros”, are constantly exposed to various situations that are harmful to health, such as the consumption of psychoactive substances. Objectives: Identify the consumption patterns of psychoactive substances in alternative transport drivers. Methods: Descriptive study with a quantitative approach, carried out on a sample of 40 “pirates/ pirateiros” drivers from the city of Oiapoque, in the State of Amapá, Brazil. A sociodemographic questionnaire was used and the Alcohol, Smoking and Substance Test (ASSIST). The data were analyzed in the Software Statistical Package for the Social Sciences (SPSS) — version: 22.0. Results: It was found that 87.5% of “pirates/ pirateiros” drivers used tobacco derivatives, 100% alcoholic beverages, 37.5% marijuana, 15% cocaine and crack, 65% amphetamine, 2.5% inhalants and deny use of hypnotics, sedatives, hallucinogens and opioids. Through the ASSIST questionnaire on Consumption Patterns, it was found that 62.5% had occasional use for marijuana and that 86.4% and 67.6% resorted to the abusive use of amphetamine and tobacco derivatives, respectively. Regarding the consumption of alcoholic beverages, 28.2% showed an indication of dependence. Conclusions: The results show that more specific research is needed to better understand the vulnerable situation of the “pirates/ pirateiros”. It emerges from research that it is necessary to encourage professionals to develop concrete health education actions for this professional category.